PENGARUH KOMPETENSI, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI BAPPEDA LITBANG KOTA PALEMBANG - Dea Umilia Savira; Fauziah Afriyani; Emilda Emilda (Institut Teknologi dan Bisnis Dewantara, 2023)
The problem of this research is How Competence, Motivation and Work Discipline Influence the Performance of BAPPEDA LITBANG Employees in Palembang City. This study aims to determine the Effect of Competence, Motivation and Work Discipline on the Performance of BAPPEDA LITBANG Employees in Palembang City. The research used quantitative methods with sampling, namely saturated sampling (census) of 80 respondents. Data analysis techniques used were validity, reliability, normality, multicollinearity, heteroscedasticity, multiple linear analysis, t test, F test and R2 test. Data processing was carried out using the SPSS version 24 application. Based on the research, it was found that: 1) Competence has a positive and significant effect on the performance of BAPPEDA LITBANG employees in Palembang City with tcount = 2.064 and sig. 0.042, 2) Motivation has a positive and significant effect on the performance of BAPPEDA LITBANG Palembang employees with tcount = 7.196 and sig. 0.000, 3) Work discipline has a positive and significant effect on the performance of BAPPEDA LITBANG Palembang City employees with tcount = 2.830 and sig. 0.006, 4) Competence, motivation and work discipline have a positive and significant effect on the performance of BAPPEDA LITBANG employees in Palembang City with Fcount = 30.245 and sig. 0.000.